2005
DOI: 10.1128/jb.187.12.3950-3959.2005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Conjugative Transfer of R27: Role of Chromosome- and Plasmid-Encoded Hha and H-NS Proteins

Abstract: IncHI plasmids encode multiple-antibiotic resistance in Salmonella enterica serovar Typhi. These plasmids have been considered to play a relevant role in the persistence and reemergence of this microorganism. The IncHI1 plasmid R27, which can be considered the prototype of IncHI plasmids, is thermosensitive for transfer. Conjugation frequency is highest at low temperature (25 to 30°C), decreasing when temperature increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 48 publications
4
66
0
Order By: Relevance
“…These results show that the Hha-YdgT proteins participate in the regulation of plasmid pSLT conjugation. The par- ticipation of Hha-like proteins in the modulation of conjugative plasmid transfer has also been reported previously for the IncH1 plasmid R27 (15). These results show that Hha-like proteins negatively modulate the expression of horizontally acquired genes in enteric bacteria, either directly or indirectly.…”
supporting
confidence: 57%
“…These results show that the Hha-YdgT proteins participate in the regulation of plasmid pSLT conjugation. The par- ticipation of Hha-like proteins in the modulation of conjugative plasmid transfer has also been reported previously for the IncH1 plasmid R27 (15). These results show that Hha-like proteins negatively modulate the expression of horizontally acquired genes in enteric bacteria, either directly or indirectly.…”
supporting
confidence: 57%
“…The decreased transcript levels of an operon in Tra1 encoding non-Mpf proteins would indicate that a global temperature regulator is controlling R27 conjugation genes in the Tra1 and Tra2 region. A recent analysis of the effect of temperature on R27 transcription has revealed that H-NS and HhaA proteins have an inhibitory effect on the transcription of a number of Tra1 and Tra2 genes at 33 u C (Forns et al, 2005). A comprehensive analysis of the temperature regulation of each R27 transfer gene has been recently completed (Alonso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of R100, the Hha homolog, RmoA, has been shown to act as a positive regulator of transfer (39). Several IncH plasmids have been shown to carry both H-NS and Hha homologs (5,23), which appear to play a role in regulating plasmid transfer gene expression (16). We are currently investigating the mechanism of TraJ antagonism of H-NS to determine whether it occurs through binding DNA to disrupt a repressor complex or by binding H-NS directly, thereby affecting its activity.…”
mentioning
confidence: 99%